An in vitro-transcribed circular RNA targets the mitochondrial inner membrane cardiolipin to ablate EIF4G2 + /PTBP1 + pan-adenocarcinoma - Feng, Zunyong; Zhang, Xuanbo; Zhou, Jing; Li, Qiang; Chu, Liuxi; Di, Guangfu; Xu, Zhengyuan; Chen, Qun; Wang, Ming; Jiang, Xiaochun; Xia, Hongping; Chen, Xiaoyuan (Nature cancer, 2024)
In vitro-transcribed (IVT) mRNA has arisen as a rapid method for the production of nucleic acid drugs. Here, we have constructed an oncolytic IVT mRNA that utilizes human rhinovirus type 2 (HRV2) internal ribosomal entry sites (IRESs) to selectively trigger translation in cancer cells with high expression of EIF4G2 and PTBP1. The oncolytic effect was provided by a long hGSDMD -F1L mutant mRNA sequence with mitochondrial inner membrane cardiolipin targeting toxicity that triggers mitophagy. Utilizing the permuted intron-exon (PIE) splicing circularization strategy and lipid nanoparticle (LNP) encapsulation reduced immunogenicity of the mRNA and enabled delivery to eukaryotic cells in vivo. Engineered HRV2 IRESs-GSDMD -F1L circRNA-LNPs (GSDMD circRNA) successfully inhibited EIF4G2 /PTBP1 pan-adenocarcinoma xenografts growth. Importantly, in a spontaneous tumor model with abnormal EIF4G2 and PTBP1 caused by KRAS G12D mutation, GSDMD circRNA significantly prevented the occurrence of pancreatic, lung and colon adenocarcinoma, improved the survival rate and induced persistent KRAS G12D tumor antigen-specific cytotoxic T lymphocyte responses.